2020
DOI: 10.1001/jamanetworkopen.2020.0202
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mutational Burden From Tumor-Only Sequencing Compared With Germline Subtraction From Paired Tumor and Normal Specimens

Abstract: IMPORTANCE Tumor mutation burden (TMB) is an emerging factor associated with survival with immunotherapy. When tumor-normal pairs are available, TMB is determined by calculating the difference between somatic and germline sequences. In the case of commonly used tumor-only sequencing, additional steps are needed to estimate the somatic alterations. Computational tools have been developed to determine germline contribution based on sample copy state, purity estimates, and occurrence of the variant in population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 18 publications
(31 reference statements)
4
35
0
Order By: Relevance
“…Overestimation of somatic variants is a problem when facing the tumor of a patient from any region or ancestry without a reference genome informative of the genetic variation in that specific population. This issue is critical for therapy determinants such as the tumor mutational load, which should be carefully interpreted in these patients 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Overestimation of somatic variants is a problem when facing the tumor of a patient from any region or ancestry without a reference genome informative of the genetic variation in that specific population. This issue is critical for therapy determinants such as the tumor mutational load, which should be carefully interpreted in these patients 39 .…”
Section: Discussionmentioning
confidence: 99%
“…TMB-H status is now an FDA-approved patient selection biomarker for ICI therapy. Because the collection of patient-matched germline samples is still not a common practice in clinic, TMBs are routinely estimated using tumor-only sequencing which led to significantly inflated TMB estimates 4 . Here we demonstrate that TMB inflations are racially disparate with significantly higher inflated TMBs in the tumors from Black patients due to the under-representation of minority groups in public variant DBs for variant filtering, regardless whether all (Figs.…”
Section: Comparative Estimations Of Tmbmentioning
confidence: 99%
“…peripheral blood) are not routinely collected in clinic for germline analysis, TMB is often calculated from tumor-only sequencing relying on public germline variant databases (DBs) to filter out non-somatic polymorphisms. We previously reported that filtering based on public DBs significantly inflated TMB 4 . In this study, we investigated the impact of minority group representation in these DBs and hypothesized that TMB would be more greatly inflated in under-represented groups.…”
mentioning
confidence: 99%
“…Additionally, tyrosine kinase inhibitors may serve as clinical therapy for metastatic NSCLC patients harboring epidermal growth factor receptor (EGFR)-enhancing mutations [8]. Despite advances in surgical therapy, chemotherapy, and radiotherapy during the past 20 years that resulted in the increased survival time in NSCLC patients, the prognosis of NSCLC has not substantially improved, owing to the tumor mutational burden and the heterogeneity of the disease [4,[9][10][11]. Thus, it is imperative to explore novel strategies to prolong patient survival time.…”
Section: Introductionmentioning
confidence: 99%